Cooperative Control Design A Systematic, Passivity-Based Approach - Bai, He.; Arcak, Murat; Wen, John.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Cooperative Control Design: A Systematic, Passivity-Based Approach discusses multi-agent coordination problems, including formation control, attitude coordination, and agreement. The book introduces passivity as a design tool for multi-agent systems, provides exemplary work using this tool,and illustrates its advantages in designing robust cooperative control algorithms. The discussion begins with an introduction to passivity and demonstrates how passivity can be used as a design tool for motion coordination.This is followed by adaptive designs for reference velocity recovery, including a basic design and a modified design with enhanced parameter convergence properties. Formation control is presented as an example illustrating the passivity-based framework and its adaptive designs. The coverage is concluded with a comprehensive discussion of the agreement problem with examples using attitude dynamics and Euler- Lagrangian systems. Cooperative Control Design: A Systematic, Passivity-Based Approach is an ideal volume for researchers and engineers working in control and engineering design.
1 Introduction -- 2 Passivity As a Design Tool for Cooperative Control -- 3 Adaptive Design for Reference Velocity Recovery: Internal Model Approach -- 4 Adaptive Design for Reference Velocity Recovery: Parameterization Approach -- 5 Attitude CoordinationWithout Inertial Frame Information -- 6 The Agreement of Euler-Lagrange Systems -- 7 Synchronized Path Following -- 8 Cooperative Load Transport -- 9 Caveats for Robustness.
Keywords: Engineering; Systems theory; Vibration; Engineering; Control; Vibration, Dynamical Systems, Control; Systems Theory, Control